2015
DOI: 10.2215/cjn.02440314
|View full text |Cite
|
Sign up to set email alerts
|

Handling of Drugs, Metabolites, and Uremic Toxins by Kidney Proximal Tubule Drug Transporters

Abstract: The proximal tubule of the kidney plays a crucial role in the renal handling of drugs (e.g., diuretics), uremic toxins (e.g., indoxyl sulfate), environmental toxins (e.g., mercury, aristolochic acid), metabolites (e.g., uric acid), dietary compounds, and signaling molecules. This process is dependent on many multispecific transporters of the solute carrier (SLC) superfamily, including organic anion transporter (OAT) and organic cation transporter (OCT) subfamilies, and the ATP-binding cassette (ABC) superfamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
214
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 228 publications
(216 citation statements)
references
References 115 publications
1
214
0
1
Order By: Relevance
“…This requires establishment of a permeability barrier (mediated by tight junctions), expression of appropriate ABC and SLC drug and solute transporters, as well as drug-metabolizing enzymes. For example, the major transporter of many organic anion drugs, toxins, and metabolites, OAT1 (originally identified as NKT) must be expressed on the basolateral surface of the proximal tubule cell (Lopez-Nieto et al, 1997;Nigam et al, 2015b;Wu et al, 2015;Zhu et al, 2015); when this gene is deleted, there is considerable loss of renal transport of many organic anion drugs, toxins, and metabolites (Eraly et al, 2006;Truong et al, 2008;Nagle et al, 2011;Torres et al, 2011;Wikoff et al, 2011). Although there is some commonality of expressed genes, they are often differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
“…This requires establishment of a permeability barrier (mediated by tight junctions), expression of appropriate ABC and SLC drug and solute transporters, as well as drug-metabolizing enzymes. For example, the major transporter of many organic anion drugs, toxins, and metabolites, OAT1 (originally identified as NKT) must be expressed on the basolateral surface of the proximal tubule cell (Lopez-Nieto et al, 1997;Nigam et al, 2015b;Wu et al, 2015;Zhu et al, 2015); when this gene is deleted, there is considerable loss of renal transport of many organic anion drugs, toxins, and metabolites (Eraly et al, 2006;Truong et al, 2008;Nagle et al, 2011;Torres et al, 2011;Wikoff et al, 2011). Although there is some commonality of expressed genes, they are often differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
“…There has recently been a call for more systematic analyses of the roles of these transporters, particularly the SLCs, in metabolism and signaling (1). There is also growing evidence showing relevance of OAT1 to metabolic disease, including chronic kidney disease (15,25,58). Taken together with the finding that these highly conserved drug transporters are differentially and highly expressed in various epithelial tissues lining body fluid compartments, it has been hypothesized that they potentially participate in remote communication ("remote sensing and signaling") between organs and organisms (2-4, 7, 9, 10, 27).…”
Section: Table 1 Top Pathways Affected By Oat1 Deficiency As Determinmentioning
confidence: 99%
“…A simulation study found that reducing the PTCPGK parameter in MechKiM by 15-fold was needed, in addition to changing GFR, to recover the observed AUC ratio between severe renal impairment and normal renal function subjects (39). However, other potential causes of reduced renal secretion include a downregulation of transporter expression, increased internalisation of renal drug transporters, and inhibition of transporters by uremic toxins that can accumulate in renal impairment (66)(67)(68). As accounting for reduced tubular secretion in a mechanistic manner is challenging, an alternative approach is to empirically estimate the extent that tubular secretion is reduced for several drugs, and apply this as a disease-specific scaling factor (69).…”
Section: Assessing Dosage Adjustment In Chronic Kidney Diseasementioning
confidence: 99%